ANALISIS PENGGUNAAN KONJUNGSI DAN TANDA BACA DALAM TEKS LHO PADA SISWA SMA KELAS X - Bella Novita; Endri Luki Pauji; Fitri Meliyarianti; Rochmat Tri Sudrajat (IKIP Siliwangi, 2018)
This study aims to describe the erroneous use of conjunctions and grammar in the Indonesian language by high school students of class X. The purpose of this study are as follows: (1) exposing errors in using conjunction on the student assignment sheet of observation report and (2) language error on the student assignment sheet of observation report. This research used the descriptive qualitative method of content analysis approach with a sample of an observation result of X class high school student which amounted to 4. Errors found consisted of misplacement of conjunction and misuse of punctuation. Factors cause, among others: the mastery of the linguistic rules of students less, inaccuracy in writing, lack of motivation to write, and the lack of vocabulary students. Efforts are made to overcome these factors by way of, implementing learning to write with process approach, improve the mastery of students' language rules by reading, and increase writing exercises.